Species composition of ichthyoplankton assemblages: a response to seasonal temperature changes - KESKIN, ÇETIN; PAULY, DANIEL (Mediterranean Marine Science, 2019)
The ‘mean temperature of the catch’ (MTC; Cheung et al. 2013, Nature 497: 365-368.) was computed for 59 ichthyoplankton surveys conducted in several regions of the Eastern Mediterranean (off the coasts of Greece and Turkey) and in the Black and Marmara Seas. This covered 162 fish species whose preferred temperatures (PTs) were derived mainly from the data used to derive Aquamaps (see www.aquamaps.org). The (geometric mean) MTCs estimates from these 59 surveys correlated strongly with observed sea surface temperatures (SSTs), once account of the sampling regions was taken. Here, this relationship is quantified using a Type II or ‘functional’ (multiple) regression. Overall, the results suggested that the MTC could be an important descriptor of the taxonomic composition and temperature affinities of ichthyoplankton assemblages.